Brain Microbleeds: Distribution and Influence on Hematoma and Perihematomal Edema in Patients with Primary Intracerebral Hemorrhage. Issue 2 (1st April 2013) - Lin, Wei-Ming; Yang, Tse-Yen; Weng, Hsu-Huei; Chen, Chih-Feng; Lee, Ming-Hsueh; Yang, Jen-Tsung; Jao, Shaner Yeun Ng; Tsai, Yuan-Hsiung
Brain microbleed is a marker of small vessel microhemorrhagic or microaneurysmal lesions, which may induce intracerebral hemorrhage (ICH). This study to prospectively evaluated the association between microbleeds, hematoma and perihematomal edema volume, and various clinical data, as well as patient outcome. Thirty-one patients with ICH and 31 healthy age-matched subjects were enrolled in our study. They were divided into two groups according to the presence or absence of microbleeds detected by MRI. Serial clinical and laboratory data were recorded. Modified Rankin Scale and Barthel Index were estimated three months after hemorrhage. The major location of microbleeds among patients with ICH was the basal ganglia. The volume of perihematomal edema was correlated with the initial hematoma volume on the first, fifth and seventh days after hemorrhage in patients with microbleeds. For patients without microbleeds, this correlation was also significant on the seventh day. Cerebral microbleeds in patients with ICH, especially in the basal ganglia region, represent micro-angiopathy, and are associated with leakage of blood and formation of perihemorrhage edema. Brain microbleeds found in patients with ICH warrant further investigation for evaluation of stroke risk.